1981
DOI: 10.1063/1.1136633
|View full text |Cite
|
Sign up to set email alerts
|

Microwave spectrometer for the detection of transient gaseous species

Abstract: A microwave spectrometer and associated apparatus for the detection of unstable free radical species is described. The spectrometer, which operates over a frequency range from 66 to 73 GHz, consists of a tunable Fabry-Perot resonator followed by superhetrodyne detection for high sensitivity at low power levels. The resonator tuning is accomplished by means of a computer controlled stepping motor and by a piezoelectric transducer which also permits the use of source modulation and phase sensitive detection at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The fit of Melen et al [34] included rotational lines in v=0-3, from both their assignments of an ATMOS (1985) [39] solar spectrum and laboratory measurements, and rovibrational laboratory data from Maillard et al [13]. Hyperfine rotational data in v=0-3 from several other studies [40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58] were also included in the fit by Melen et al [34]. Despite hyperfine structure not being included in the results of Bernath and Colin [33], they took some of this information into account by adding pseudotransitions to the fit, between e and f parity levels and various J levels ("Λ-doubling data"), based on the term values calculated by Melen et al [34].…”
Section: Introductionmentioning
confidence: 99%
“…The fit of Melen et al [34] included rotational lines in v=0-3, from both their assignments of an ATMOS (1985) [39] solar spectrum and laboratory measurements, and rovibrational laboratory data from Maillard et al [13]. Hyperfine rotational data in v=0-3 from several other studies [40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58] were also included in the fit by Melen et al [34]. Despite hyperfine structure not being included in the results of Bernath and Colin [33], they took some of this information into account by adding pseudotransitions to the fit, between e and f parity levels and various J levels ("Λ-doubling data"), based on the term values calculated by Melen et al [34].…”
Section: Introductionmentioning
confidence: 99%
“…Initial interest in the Λ-doubling bands, both located beyond 1 cm in wavelength, resulted in a wealth of high quality laboratory measurements that will not be reviewed here since much of the initial work was culminated and documented in ref and then again in the recent compilation by Matrin-Drumel et al The compilation includes a variety of spectra sources. …”
Section: Introductionmentioning
confidence: 99%
“…By giving zero weights for the transitions with low signal-to-noise ratios, the observed transitions in table 1 were submitted to a least squares fitting to determine the spectroscopic constants. This fitting included also the microwave frequencies of Ã-doublet transitions (table 2) reported by Gottlieb et al [11] and Kolbe et al [12], and farinfrared transition frequencies (table 3) measured by Morino et al [14]. These transition frequencies were corrected for hyperfine structure and were weighted according to frequency precision.…”
Section: Observed Spectrum and Analysismentioning
confidence: 99%
“…Gottlieb et al [11] observed the same Ã-doublet transitions using a molecular beam microwave spectrometer. Kolbe et al [12] reported an extended measurement of a high-J transition. Comben et al [13] measured the far-infrared laser magnetic resonance spectrum of the pure rotational transitions, to determine the spin-orbit interaction, rotational, centrifugal distortion, spinrotation coupling constants.…”
Section: Introductionmentioning
confidence: 97%